PSYCHORELIGIOUS THERAPY INTERVENTION OF DZIKIR FOR PATIENTS WITH HALLUCINATION DISORDERS - Widodo, Andrian Aziz; Rahayu, Sri (LPPM Univ. Ibn Khaldun Bogor, 2024)
Introduction: Mental health has become a global issue, with hallucinations being one of the symptomatic indication of schizophrenia or positive psychosis. Objective: This research aims to analyze various studies regarding the application of psychoreligious dzikir therapy for patients with hallucination disorders. Method: The method used in this research is a literature review, utilizing Google Scholar with keywords related to dzikir psychoreligious therapy for hallucination disorders. Results: The psychoreligious dzikir therapy intervention has shown a significant impact in reducing and managing hallucination disorders in patients. Recommendation: As a non-pharmacological therapy, psychoreligious dzikir therapy is highly recommended for implementation in managing patients with hallucination disorders.